The Effect of The Thematic Storytelling Method on The Reading Liteacy of Children 5-6 Years Old at Kindergarten: Pengaruh Metode Bercerita Tematik terhadap Literasi Membaca Anak Usia 5-6 Tahun di Taman Kanak-Kanak - Chamidah, Yuyun; Aulina, Choirun Nisak (Indonesian Journal of Education Methods Development, 2023)
This study aims to determine the influence and how much influence the thematic storytelling method has on the reading literacy of children aged 5-6 years in InsanMandiri Kindergarten Sidoarjo. This research is an experimental research that requires experimental and control samples as data analysis. The population in this study was students at InsanMandiri Kindergarten, with a sample of 20 children each as an experimental sample and a control sample. Data collection techniques used are tests and documentation. Data analysis method using independent test t.Based on the results of the study obtained a significance value of 0.000 <0.05, it can be concluded that there is an average difference between the research samples. Meanwhile, from the mean, it can be seen that the test result score for the experimental class is 9.55 higher than the control class, which is 6.35. So it can be concluded that there is an effect of the thematic storytelling method on the reading literacy of children aged 5-6 years in TK InsanMandiriSidoarjo, amounting to 9.55. The student's thematic storytelling activity is stimulated to understand stories that have been read or heard, and it may help the student to answer questions about the reading and thus make it easier for the student to retell the reading or the story in his own language.